2013
DOI: 10.1155/2013/409302
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Land Cover Change on the Near-Surface Temperature in the North China Plain

Abstract: This study first tested and verified the ability of the Weather Research and Forecasting (WRF) model to simulate the near-surface temperature in the North China Plain. Then the static land cover data in the WRF were replaced, and thereafter the modified WRF model was used to explore the impacts of land cover change on the near-surface temperature in the North China Plain in year 1992 and year 2005. The results indicated that the land cover change in the North China Plain, which was characterized by the regiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
2

Year Published

2014
2014
2016
2016

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 10 publications
0
23
2
Order By: Relevance
“…One worst-case scenario prediction offers a 4.0°C increase in global air temperature by the end of the century (Parry et al, 2007), which triggers a 2-3°C increase in water temperature (Morrill et al, 2005). On the other hand, Qu et al (2013) reported that increase in air temperature varied with the land cover in north China during 1992-2005. One promising approach to address this issue may be to use a hydrothermal simulation model, which calculates runoff and water temperature based on meteorological and land cover data (e.g., Nukazawa et al, 2011), to project future thermal regimes.…”
Section: Discussionmentioning
confidence: 99%
“…One worst-case scenario prediction offers a 4.0°C increase in global air temperature by the end of the century (Parry et al, 2007), which triggers a 2-3°C increase in water temperature (Morrill et al, 2005). On the other hand, Qu et al (2013) reported that increase in air temperature varied with the land cover in north China during 1992-2005. One promising approach to address this issue may be to use a hydrothermal simulation model, which calculates runoff and water temperature based on meteorological and land cover data (e.g., Nukazawa et al, 2011), to project future thermal regimes.…”
Section: Discussionmentioning
confidence: 99%
“…Climate change in China has been simulated in recent years by many scholars. Qu et al (2013) used WRF to explore the impacts of land cover change on the near-surface temperature in a research in Northern China Plain. The RegCM3 can reproduce the observed spatial structure of surface air temperature and precipitation well.…”
Section: Case Studies Of Land Use Impacts On Surface Climatementioning
confidence: 99%
“…Wu and Fu (2013) used a linear fitting method to estimate the change of precipitation intensity spectra at different spatial scales in China. Qu et al (2013) used WRF to explore the impacts of land cover change on the near-surface temperature in a research in Northern China Plain. They tested and verified the ability of WRF to simulate the near-surface temperature in the study area.…”
Section: Case Studies Of Land Use Impacts On Surface Climatementioning
confidence: 99%